INDICES AND FECUNDITY OF A THREATENED FRESHWATER CATFISH MYSTUS MONT ANUS - Arockiaraj, A. Jesu; Haniffa, M. A.; Seetharaman, S.; Singh, S. P. (Journal of Indian Fisheries Association, 2015)
Fecundity of threatened catfish JJfystus montanus was estimated from acollection of gravid females, which ranged from 290 to 27,972 according tobody length and weight. The relationship, between fecundity and BL, BW, GLand GW was analyzed by linear regression, which showed both positive andnegative correlation. Gonado-somatic index (GSI), hepato-somatic index (HSI)and spleen-somatic index (SSI) ranged from 0.135 to 21.28, 0.358 to 21.33 and0.126 to 1.08 in females and the correponding values for males were 0.17 toÂ· 10.68, 0.619 to 3.25 and 1.25 to 2.33 respectively.Keywords: Fecundity, indices, threatened catfish, Mystus montanus